Application of P5 based on Local Wisdom in ELT - Aditama, Madya; shofyana, maila huda (Universitas Muhammadiyah Jember, 2024)
Fulfilling students' needs in learning is a major factor in the educational process. However, there are still many misconceptions about the application of Merdeka Curriculum among teachers, resulting in the goal of competence in the Pancasila Student Profile not being achieved. Project-based learning is applied as an effort to provide different treatment to each student who has different characteristics and needs. The diversity of Batang Regency's local wisdom and local cultures that are starting to become extinct is a potential that should be preserved. The purpose of this study is to analyze local wisdom-based differentiation learning applied by high school and vocational school teachers in Batang Regency in the Merdeka Curriculum. This research is a qualitative research with a phenomenological approach where data collection uses questionnaires, interviews and observations with 20 teachers; the collected data is analysed by grouping according to the level and target competencies. Based on the results of the study, the dimensions of independence, critical reasoning and creativity are the 3 main characters that are reflected in every P5 lesson conducted by English teachers in Batang district.